2021
DOI: 10.3329/imcjms.v14i2.52833
|View full text |Cite
|
Sign up to set email alerts
|

Commentary about open-label randomized controlled study of ivermectin in mild to moderate COVID-19

Abstract: not available Ibrahim Med. Coll. J. 2020; 14(2): 67-68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In a letter to the editor about Podder et al, Meneses pointed out important ethical issues. He observed that the authors mentioned approval of their study by the director of the health center, but apparently there was methodological and ethical evaluation by an institutional board [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a letter to the editor about Podder et al, Meneses pointed out important ethical issues. He observed that the authors mentioned approval of their study by the director of the health center, but apparently there was methodological and ethical evaluation by an institutional board [ 76 ].…”
Section: Discussionmentioning
confidence: 99%